Lipid status in phyisiological non-complicated pregnancy - Ardalić Daniela; Stefanović Aleksandra; Spasić Slavica; Zeljković Aleksandra; Vekić Jelena; Spasojević-Kalimanovska Vesna; Jelić-Ivanović Zorana; Mandić-Marković Vesna; Miković Željko; Cerović Nikola (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Specifically altered lipid profile and physiological hyperlipidemia during pregnancy are considered essential for the normal course of pregnancy and fetal development. This specific alteration of the lipid profile raises the questions about potential proaterogenic effect of these altered lipid parameters during pregnancy and its influence on the development of cardiovascular disease in women later in life. Research topic was also the association of altered lipid profile during pregnancy with the development of complications in pregnancy, especially gestational diabetes, hypertension and preeclampsia. Through the mediation of cholesterol ester transfer protein (CETP), the activity of which grows in mid-gestation, there are exchanges of the triglycerides between VLDL and LDL or HDL particle, which leads to increased accumulation of triglycerides in these particles, causes them to become smaller and denser with much greater atherogenic potential. These changes in lipid profile point out that a large number of pregnancies increase risk of development of cardiovascular diseases later in life. In order to optimize the predictive capacity of the lipid profile during pregnancy, it is recommended to determine the indexes of lipid.